A low‐profile dual‐band circularly polarized antenna based on artificial magnetic conductor. Issue 3 (23rd January 2021) - Zhao, Gang; Zhang, Fushun; Yang, Kaiwen; Li, Guang
Abstract: A low‐profile dual‐band circularly polarized (CP) antenna with wide beamwidth is proposed in this article. The proposed antenna is composed of three layers of spiral patches, an artificial magnetic conductor (AMC) reflector and a four‐feed network. The three‐layer spiral patches as a quadrifilar helix antenna are employed to achieve dual‐band CP radiation. Then, a metal ground is replaced by one square‐shaped AMC surface to improve the antenna performance. With these antenna structures, the antenna size is only 0.36λ0  × 0.36λ0  × 0.106λ0 at 1.268 GHz. The antenna exhibits the impedance bandwidth ranging from 1.17 to 1.39 GHz and 1.49 to 1.58 GHz (|S11 | < −10 dB). Furthermore, the proposed antenna has excellent axial ratio beamwidths of 171° at 1.268 GHz and 201° at 1.561 GHz. With these excellent characteristics, the designed antenna can be well applied to global navigation satellite systems.